1999
DOI: 10.1590/s0366-69131999000100005
|View full text |Cite
|
Sign up to set email alerts
|

Síntese de pós de zircônia cúbica policristalina

Abstract: Este trabalho aborda a preparação de pós cerâmicos de zircônia (ZrO2) estabilizada com um concentrado de óxidos de Ítrio e terras raras (OTR). O objetivo principal deste trabalho é a obtenção de eletrólitos sólidos de zircônia para aplicação em sensores de oxigênio. O método de preparação adotado foi o de co-precipitação química dos respectivos hidróxidos em meio amoniacal (NH4OH). Foram preparadas amostras variando a concentração de OTR, entre 10 e 35% em massa. São apresentados e discutidos os resultados de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Ceramic of alumina are essentially used as structural materials due to its high elastic modulus, high resistance to chemical attack and stability at elevated temperatures [1]. Aluminazirconia composite presents mechanism of tenacity that are depend on the inclusions dimensions, to the induced tensions by monoclinic-tetragonal transformations, to the inclusions around the crack that can propagate and microcrack [2,3]. Recent works [4,5] have been showed that the nanometrics inclusions of zirconium in the alumina matrix can give inhibition of the grains growth and increase the mechanical resistance of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic of alumina are essentially used as structural materials due to its high elastic modulus, high resistance to chemical attack and stability at elevated temperatures [1]. Aluminazirconia composite presents mechanism of tenacity that are depend on the inclusions dimensions, to the induced tensions by monoclinic-tetragonal transformations, to the inclusions around the crack that can propagate and microcrack [2,3]. Recent works [4,5] have been showed that the nanometrics inclusions of zirconium in the alumina matrix can give inhibition of the grains growth and increase the mechanical resistance of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the development of alumina composite with nanometric zirconium inclusions has been prepared by chemical methods, such as, sol-gel [7], co-precipitation [8] and electrophoretic deposition (EPD) [9], presenting good results in terms of mechanical properties [2][3][4][5]. The ceramic powders obtained from chemical methods present as main characteristics high reactivity and good chemical homogeneity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Essas perdas de massa são atribuídas à saída de substâncias voláteis, água adsorvida e água estrutural. O pico exotérmico registrado na curva ATD a uma temperatura aproximada de 450 0 C é atribuído à cristalização do material, isso sugere que a zircônia irregular é rearranjada a um crescimento periódico do retículo cristalino 15,16,17 . Com relação aos eventos térmicos dos materiais impregnados com ouro, verificou-se uma perda de massa contínua de 50 a 200 o C e um pico endotérmico centrado em 80 o C, que pode ser relacionado com a saída de água e voláteis.…”
unclassified